1995
DOI: 10.2519/jospt.1995.22.3.95
|View full text |Cite
|
Sign up to set email alerts
|

Backward Walking at Three Levels of Treadmill Inclination: An Electromyographic and Kinematic Analysis

Abstract: recent vears, the predominant philosophv of physical therapists and athletic trainers in treating lower extremity injuries has focused on the use of closed kinetic chain exercises. This is based on both observational and experimental data that suggest such exercises are more effective, safer, and more functional than previouslv emploved open kinetic chain exercises (3,8,9,12,20,23,29,30,37,58,41). M'hile a variety of techniques are typically used to create a closed kinetic chain environment, one that has evoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 25 publications
2
51
0
2
Order By: Relevance
“…If a certain amount of exercise time is given, a training task that makes lower extremity muscles discharge myogenic potential in a given time is generally effective. It is reported that discharged myogenic potential capacity is higher at various sites in backward walking than in forward walking [1][2][3][4] . Both forward and backward treadmill training were performed over the same period of time and with the same exercise tolerance in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If a certain amount of exercise time is given, a training task that makes lower extremity muscles discharge myogenic potential in a given time is generally effective. It is reported that discharged myogenic potential capacity is higher at various sites in backward walking than in forward walking [1][2][3][4] . Both forward and backward treadmill training were performed over the same period of time and with the same exercise tolerance in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Walking backwards is different from walking forwards as toe contact is made at the initial foot contact during the stance phase of the gait cycle and the leg is swung, while conscious of the hip extensors' position, in the swing phase. Moreover, differences in muscle activity patterns and myogenic potentials occur while walking backwards compared to walking forwards [1][2][3][4] . For this reason, walking backwards can lead to effects that are not produced by walking forwards as well as increasing exercise tolerance 2,3,5,6) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, cycling has been used in clinical settings to successfully rehabilitate traumatic knee injuries in athletes (Flynn & Soutas-Little, 1993;Cipriani et al, 1995;Eisner et al, 1999). Researchers hypothesize that cycling backwards on a cycle ergometer increases muscle fiber activation of the lower-extremity musculature, improving strength.…”
Section: Discussionmentioning
confidence: 99%
“…Previousstudies have mostly included analysis of gait characteristics (Bergmann, Graichen, & Rohlmann, 1993;Burnfield, 2010) and muscle activities (An, Kim, & Lee, 2007;Cipriani, 1995;McArdle, Katch, & Katch, 2001) according totreadmill speed or inclination. However, muscle activity and kinematic studies on gaze angle during treadmill walking are almost non-existent.…”
Section: Kjsbmentioning
confidence: 99%